Orwell in Context - Clarke, B. author. aut Link
IX, 225 p.
Keywords: This bold new reading of Orwell's work focuses upon his representation of communities and the myths that shape them. It analyzes his interpretations of class, gender and nationality within the context of the period. The book uses a range of texts to argue that Orwell attempted to integrate 'traditional' communal identities with socialist politics.